2ln(x)-ln(5)=ln(x+10)

Simple and best practice solution for 2ln(x)-ln(5)=ln(x+10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2ln(x)-ln(5)=ln(x+10) equation:


Simplifying
2ln(x) + -1ln(5) = ln(x + 10)

Multiply ln * x
2lnx + -1ln(5) = ln(x + 10)

Reorder the terms for easier multiplication:
2lnx + -1 * 5ln = ln(x + 10)

Multiply -1 * 5
2lnx + -5ln = ln(x + 10)

Reorder the terms:
-5ln + 2lnx = ln(x + 10)

Reorder the terms:
-5ln + 2lnx = ln(10 + x)
-5ln + 2lnx = (10 * ln + x * ln)
-5ln + 2lnx = (10ln + lnx)

Solving
-5ln + 2lnx = 10ln + lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-10ln' to each side of the equation.
-5ln + -10ln + 2lnx = 10ln + -10ln + lnx

Combine like terms: -5ln + -10ln = -15ln
-15ln + 2lnx = 10ln + -10ln + lnx

Combine like terms: 10ln + -10ln = 0
-15ln + 2lnx = 0 + lnx
-15ln + 2lnx = lnx

Add '-1lnx' to each side of the equation.
-15ln + 2lnx + -1lnx = lnx + -1lnx

Combine like terms: 2lnx + -1lnx = 1lnx
-15ln + 1lnx = lnx + -1lnx

Combine like terms: lnx + -1lnx = 0
-15ln + 1lnx = 0

Factor out the Greatest Common Factor (GCF), 'ln'.
ln(-15 + x) = 0

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-15 + x)' equal to zero and attempt to solve: Simplifying -15 + x = 0 Solving -15 + x = 0 Move all terms containing l to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + x = 0 + 15 Combine like terms: -15 + 15 = 0 0 + x = 0 + 15 x = 0 + 15 Combine like terms: 0 + 15 = 15 x = 15 Add '-1x' to each side of the equation. x + -1x = 15 + -1x Combine like terms: x + -1x = 0 0 = 15 + -1x Simplifying 0 = 15 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 6(4+c)=5(c-6) | | 4v^2=-21v-5 | | 84=1x+96 | | 26z+9+11+-17z=-16+9 | | 17x-8=7x+2 | | (4/p)+(5/2)=7/p | | 22,45:0,345= | | 2/3*2/5= | | 100=10b+3g+50-.5b-.5g | | (5y-1)(5+y)=0 | | 3(4z-3)-3(2-2z)=6 | | x/9=3/2 | | 10,000^5/4 | | 5m+4*(m-4)= | | 18x^2-59x=-34 | | 5m+4(m-4)= | | 3x+30=24x-120 | | 3-1/2x=-2 | | 7x+x+8-2x+5=45 | | 6y+y+5y= | | 3xa-4xb+5xa-3xb= | | 2(4x-3)=10 | | 9x+237=4x+172 | | 4(y-2)-9=-7(-2y+5)-2y | | 11-w/2=60 | | 4x(5x+7)= | | ax^2+6ax+9a=0 | | -x+15-3x+6=-7x-4x | | (25.12^2)/(4(3.14)) | | -6/7x+17=-61 | | 7/9-5/13 | | (78x-48y)-(68x+28y)= |

Equations solver categories